Animal-Assisted Interventions: A Literature Review on Diverse Applications of Animal-Assisted Interventions in selected medical entities in different age groups - Najdek, Agnieszka; Szewczyk, Dorota; Nowak, Julia; Woźniak, Aleksandra; Cioch, Michał Jakub; Mycyk, Marcin; Kaczmarska, Urszula; Oleksy, Daria; Doman, Katarzyna; Hermanowicz, Kamil; Komada, Dawid (Journal of Education, Health and Sport, 2025)
This literature review examines the therapeutic role of Animal-Assisted Interventions (AAIs) in promoting physical and mental well-being for diverse populations. AAIs have shown positive impacts on children and adults, benefiting individuals with neurodevelopmental disorders as well as ex-military personnel. The review emphasizes the growing support for AAIs, extending beyond traditional therapy and reaching diverse groups. Numerous studies back up the favorable effects of animal-assisted treatments on children's social connections, academic progress, and emotional and physical health.